COVID-19 Infection Negative in Nasopharyngeal Swabs but Suspected in Computed Tomography and Confirmed in Bronchoalveolar Lavage Material - Robert Chrzan; Tadeusz Popiela; Maciej Małecki; Jan Skupień; Amira Bryll; Anna Grochowska (Case Reports in Infectious Diseases)
We present a case of a patient with clinical symptoms of pneumonia, negative in several polymerase chain reaction COVID-19 tests from nasopharyngeal swabs but suspected in computed tomography and finally confirmed in bronchoalveolar lavage material.